The qwality of life of patients with a sick sinus syndrome depending on the pulse blood pressure level one year after cardiac pacemaker implantation - Al-Mter Muhtadi Jabbar Abdulzahr (тронный ресурс: http://im.medicina. karazin.ua/downloads/abs/Починская тезы_05.2019.pdf, 2019)
Актуальні питання сучасної медицини: Тези доповідей XVІ Міжнародної наукової конференції студентів, молодих вчених та фахівців 28-29 березня 2019 р. – Х.: ХНУ імені В. Н. Каразіна, 2019. – C. 313-314.
Scientific supervisor: Pochynska M. V ., PhD. assistant
Keywords: sick sinus sindrom